Cytological Spectrum of Pap Smears according to the Bethesda System and its Clinical Correlation in a tertiary care centre - Dr. Pooja Awasthi Mahajan; Dr. Pooja Awasthi Mahajan; Dr. Vaishali D Kotasthane; Dr. Dhananjay S Kotasthane (International Journal of Pharma and Bio Sciences, 2024)
Uterine Cervix is an easily accessible site for various infections, inflammations, and malignancies. Cervical cancer is considered to be the fourth leading cause of death in women worldwide; therefore, it needs to be detected and treated early for better survival. The primary aim of cervical PAP smear screening is to screen and identify neoplastic lesions in the early stage, as cervical cancer can be cured if diagnosed at an early stage and treated promptly. In various pap smear studies, the frequency of non-neoplastic lesions and infections of the cervix is very common. The study aimed to describe the cytomorphological spectrum of lesions of the Uterine Cervix, its clinical correlation, and the categorization of the lesions according to the Bethesda System of Classification 2014. The study’s objective was to determine the preference of age and parity in different lesions of the Uterine Cervix to correlate and compare the cytological findings with histomorphological findings. The observation study included 505 women aged 21-65 attending gynecological OPD who underwent conventional pap smears from Dec 2020 to Nov 2022. Out of 505 pap smears studied, most utero-cervical lesions screened were in the 4th decade (43.56%) and parity three (32.87%). The most common presenting clinical symptom was leucorrhoea (45.9%), the most common infection was bacterial vaginosis (59.036%), and the most common abnormal epithelial cell lesion was HSIL (4.55%) (high-grade squamous intraepithelial lesion). Out of 505 pap smear cases, in 97 cases, histopathological correlation was done. The sensitivity of the pap smear was 83.33%, specificity :97.05%, Positive predictive Value :97.22%, and Negative predictive value :82.50%. Most cervical lesions are benign, but it is a site of shades of grey lesions, that includes cervical dysplasia to malignancy. Thus, a pap smear is an easy, cost-effective OPD procedure for the early detection of lesions of the uterine cervix.